El código Davinci / Ron Howard - Howard, Ron, 1954- (Madrid Columbia pictures, 2006)
A murder inside the Louvre, and clues in Da Vinci paintings, lead to the discovery of a religious mystery protected by a secret society for two thousand years, which could shake the foundations of Christianity.
Tom Hanks, Audrey Tautou, Jean Reno
No recomendada a menores de 13 años
Idiomas : Inglés, catalán y castellano. Subt.: castellano, inglés, danés, finlandés, noruego, sueco y portugués
Keywords: Películas cinematográficas -- DVD